2021
DOI: 10.1002/jid.3568
|View full text |Cite
|
Sign up to set email alerts
|

Aid for health, economic growth, and the emigration of medical workers

Abstract: Debates on the extent to which developing countries suffer from a brain drain often focus on the emigration of locally scarce health personnel. In this paper, we empirically examine how two potential determinants-aid for health and local income levels-affect the emigration rates of doctors and nurses from developing countries. Employing a standard gravity model of international migration, we show that aid for health has a negative effect on the emigration of both nurses and doctors. Our findings suggest that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In that sense, Vogt and König (2021) propose increased use of robotic devices and ICT to reduce employees' physical hardships and mental stress. Even though their study is focused on Japan, their findings are beneficial to both managers and policymakers in all areas with high levels of emigration of medical and nursing staff (Cabanda, 2023;Byrne, et al, 2021;Lanati & Thiele, 2021;Żuk, Żuk, & Lisiewicz-Jakubaszko, 2019, etc. ).…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, Vogt and König (2021) propose increased use of robotic devices and ICT to reduce employees' physical hardships and mental stress. Even though their study is focused on Japan, their findings are beneficial to both managers and policymakers in all areas with high levels of emigration of medical and nursing staff (Cabanda, 2023;Byrne, et al, 2021;Lanati & Thiele, 2021;Żuk, Żuk, & Lisiewicz-Jakubaszko, 2019, etc. ).…”
Section: Discussionmentioning
confidence: 99%
“…When aid is broken down in terms of sector, support for social services, partly in response to the Millennium Development Goals (MDGs), seems to reduce migration rates compared to aid aimed at increasing income through better economic infrastructure or productive sectors (Dustmann & Okatenko, 2014; Lanati & Thiele, 2018, 2020, 2021). The reason suggested is that potential migrants can only benefit from these improved social services by staying at home.…”
Section: Migration Development and Foreign Aidmentioning
confidence: 99%
“…As a result, in 2022, low-skilled workers (34%), skilled workers (30%) and housemaids (25%), Kuwait (79,123), Qatar (71,954), Saudi Arabia (53,702) and UAE (35,563) hosted the highest numbers of Sri Lankan employees [5]. Nevertheless, Lanati and Thiele [34] findings reveal a lower migration rate of low-income individuals to the Organisation for Economic Co-operation and Development (OECD) countries, resulting in lower remittances in these destinations, primarily due to the comparatively higher cost of living than GCC countries. Chambers, Bliss [35] reported that the desire for improved economic prospects and better living standards drives many people to seek opportunities abroad, reflecting the concept of "place utility".…”
Section: Impact Of Eg On Migrationmentioning
confidence: 99%
“…Rasamoelison, Averett [30], Islam [33], Lanati and Thiele [34], Khan and Arokkiaraj [41], Tipayalai [42] Source: Authors' compilations.…”
Section: (-)mentioning
confidence: 99%